Heparin-induced thrombocytopenia: a rare presentation with skin necrosis - Filipa David; Ana Catarina Trigo; José Ribeiro; Joana Cancela (PAGEPress Publications, 2023)
Heparin-induced thrombocytopenia is the most clinically relevant non-haemorrhagic complication of heparin and is characterised by the presence of anti-PF4/heparin-IgG antibodies. The circulating PF4/heparin-IgG immune complex binds to platelets via their FcyIIa receptors, activating them and promoting their aggregation, with consequent platelet consumption, thrombocytopenia and thrombotic phenomena. Despite thrombocytopenia, this condition is not typically associated with bleeding complications. Instead, thrombosis is the most serious complication of Heparin-induced thrombocytopenia, contributing to increased morbidity and mortality. Thrombotic events can be venous and arterial, such as deep vein thrombosis, pulmonary embolism, myocardial infarction, and thrombotic stroke. Skin necrosis at the site of heparin injections is a rare but well-described manifestation of Heparin-induced thrombocytopenia. We report a case of Heparin-induced thrombocytopenia presented as skin necrosis, highlighting the importance of recognising this potentially fatal condition and the need for an immediate cessation of all sources of heparin and its replacement by other anticoagulants.